2019
DOI: 10.1097/iae.0000000000002012
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Accident–related Open Globe Injuries

Abstract: Traffic accident-related open globe injuries had better visual outcomes than common open globe injuries. Visual outcomes in patients with traffic accident-related open globe injuries were related to the initial visual acuity. No eyes developed endophthalmitis in patients with traffic accident-related open globe injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
5
14
0
Order By: Relevance
“…Considering about gender, the result of this study is consistent with other OGI publications, either investigated for overall causes or only for traffic-related injury, which found that male was a major proportion of patients than female, even though varying in ratio [13,15,16,20,22]. This may refer to differences in physical activities between genders.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Considering about gender, the result of this study is consistent with other OGI publications, either investigated for overall causes or only for traffic-related injury, which found that male was a major proportion of patients than female, even though varying in ratio [13,15,16,20,22]. This may refer to differences in physical activities between genders.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, in road traffic-related OGI, the disparities in age range have been demonstrated. A study in US by Orr et al presented that nearly half of cases (48%) were young patients between 20 to 40 years whereas a study in Japan by Okamoto et al found that road traffic injury comprised a more proportion of elderly patients with a mean age of 50 years [20,22]. This study, similar to Zhang et al, demonstrated that the highest incidence occurred in young patients between 20 to 39 years which represented teenagers and/or early working groups [10].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Moreover, the inhomogeneous distribution of affected age groups may reflect different daily activities of the at risk populations, therefore the demographic data should be taken into consideration when implementing the safety measurements in each country. www.nature.com/scientificreports/ Some specific circumstances were more likely to cause globe rupture than others [18][19][20][21][22][23] . A study by Feng et al reported that violence, explosion, and traffic were the most frequent causes leading to severe ruptured eyes requiring vitreoretinal surgery 24 .…”
Section: Discussionmentioning
confidence: 99%